Measuring recovery after open lower limb fractures: combined objective functional tests and global perceived recovery outperform narrower metrics and a standard generic patient reported outcome measure - Ian Pallister (BMC Musculoskeletal Disorders, 2021)
Open lower limb fractures are serious injuries requiring combined ortho-plastic surgery and have significantly worse outcomes than similar closed fractures. There is little objective published data to determine which functional outcome measures best reflect progress or completeness of physical recovery.Our hypothesis was that objective measures combining strength, mobility and balance would better reflect recovery than isolated parameters (e.g. range of motion ROM) and would compare well to patients’ perceived recovery.